2005
DOI: 10.1182/blood.v106.11.6.6
|View full text |Cite
|
Sign up to set email alerts
|

Study of Lenalidomide Plus Dexamethasone Versus Dexamethasone Alone in Relapsed or Refractory Multiple Myeloma (MM): Results of a Phase 3 Study (MM-010).

Abstract: High-dose dexamethasone (Dex) remains a standard therapy for relapsed or refractory MM. Lenalidomide is a novel, orally administered, immunomodulatory drug (IMiD) that has single-agent activity against MM and additive effects when combined with Dex. In this phase 3, multicenter, randomized, double-blind trial, 351 patients with relapsed or refractory MM were enrolled from clinical centers in Europe, Israel, and Australia. Patients were treated with Dex 40 mg daily on days 1–4, 9–12, and 17–20 every 28 days and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 0 publications
2
48
0
Order By: Relevance
“…The incidence of venous thromboembolism in association with the use of single agent thalidomide or lenalidomide is low and has been reported in up to 5% of patients (Singhal et al, 1999;Hussein, 2006;Richardson et al, 2006). Interestingly, the use of combination therapy, especially with dexamethasone, appears to increase this risk (Dimopoulos et al, 2005;Hussein, 2006;Knight et al, 2006). In this phase 1 study, there were no deep vein thromboses reported either for patients who received single agent pomalidomide or those who subsequently received pomalidomide and dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of venous thromboembolism in association with the use of single agent thalidomide or lenalidomide is low and has been reported in up to 5% of patients (Singhal et al, 1999;Hussein, 2006;Richardson et al, 2006). Interestingly, the use of combination therapy, especially with dexamethasone, appears to increase this risk (Dimopoulos et al, 2005;Hussein, 2006;Knight et al, 2006). In this phase 1 study, there were no deep vein thromboses reported either for patients who received single agent pomalidomide or those who subsequently received pomalidomide and dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…The MM010 (Europe and Australia) recruited 351 patients from 50 clinical sites with a median age of 63 years in the study arm and 64 years in the control arm. 50 In both the MM010 and MM009 (USA and Canada) trials, those receiving lenalidomide had significantly better ORR (61.2 and 58%, respectively) compared with dexamethasone alone (21.7 and 22.8%, respectively) with a further 28.2 and 33.5%, respectively, achieving stable disease. 51 There was also a significantly prolonged median time to progression (TTP) of 60.1 and 53.4 weeks (MM009 and MM010) in those receiving active drug, more than double that of dexamethasone-treated and placebotreated patients (20.7 and 20.6 weeks, respectively).…”
Section: Clinical Experiencementioning
confidence: 98%
“…Two key phase III randomized, multicentre, double blind placebo controlled studies using identical protocols have been carried out (Dimopoulos et al, 2005;Weber et al, 2006a) with updated results recently reported (Dimopoulos et al, 2007;Weber et al, 2007). The randomization compared lenalidomide 25 mg daily on 21 days of a 28-day cycle plus dexamethasone with dexamethasone alone.…”
Section: Phase III Trials In Relapsed and Refractory Diseasementioning
confidence: 99%
“…Myelosuppression has been identified as the most important adverse effect of lenalidomide therapy. Grade 3/4 neutropenia is reported in 16.5-24% of patients and thrombocytopenia in 11-17% patients (Dimopoulos et al, 2005;Weber et al, 2006a,b;Dimopoulos et al, 2007;Weber et al 2007, Celgene data on file). As a consequence, we recommend blood counts be carried out at two weekly intervals during the first 1-2 months of treatment and as clinically appropriate during subsequent cycles.…”
Section: Myelosuppressionmentioning
confidence: 99%
See 1 more Smart Citation